HMPDACC: a Human Microbiome Project Multi-omic data resource. Issue Volume 49:Issue D1(2021) (10th December 2020) - Creasy, Heather Huot; Felix, Victor; Aluvathingal, Jain; Crabtree, Jonathan; Ifeonu, Olukemi; Matsumura, James; McCracken, Carrie; Nickel, Lance; Orvis, Joshua; Schor, Mike; Giglio, Michelle; Mahurkar, Anup; et al.
Abstract: The Human Microbiome Project (HMP) explored microbial communities of the human body in both healthy and disease states. Two phases of the HMP (HMP and iHMP) together generated >48TB of data (public and controlled access) from multiple, varied omics studies of both the microbiome and associated hosts. The Human Microbiome Project Data Coordination Center (HMPDACC) was established to provide a portal to access data and resources produced by the HMP. The HMPDACC provides a unified data repository, multi-faceted search functionality, analysis pipelines and standardized protocols to facilitate community use of HMP data. Recent efforts have been put toward making HMP data more findable, accessible, interoperable and reusable. HMPDACC resources are freely available at www.hmpdacc.org .